Biskuit Ampas Kopi (Bis’Kop) sebagai Alternatif Snack dengan Konsep Zero Waste - Grace Marveline Lucky Hantiono; Inggritia Maestra Citra Dewi; Cindy Zakia Az-Zahra; Esteria Priyanti (Garina, 2025)
Coffee ground have great potential to be used as an additional ingredient in making biscuits. The purpose of this study is to create innovative coffee grounds biscuits that can be a promising business opportunity. This study uses a Research and Development (R&D) research design with a 4D model (Define, Design, Develop, and Disseminate). The results of this study are BIS'KOP (Biskuit Ampas Kopi) products that have a sweet taste, light coffee aroma, crunchy texture, and brown color on the biscuit part and white color on the vanilla cream part. Overall, the sensory characteristics of BIS'KOP products, including taste, aroma, texture, and color have met the expected criteria and are worthy of being marketed. BIS'KOP products can be sold at a price of IDR 24,000.00 per package containing 5 (five) pcs of BIS'KOP. Each serving of BIS'KOP can meet 5% of energy needs, 2% of protein needs, 7% of fat needs, and 5% of carbohydrate needs. Thus, it can be concluded that coffee grounds biscuits have the potential as an alternative snack with a zero waste concept.